2015
DOI: 10.1002/cncr.29274
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with suicide in patients with genitourinary malignancies

Abstract: BACKGROUND: Approximately 70% of all suicides in patients aged >60 years are attributed to physical illness, with higher rates noted in patients with cancer. The purpose of the current study was to characterize suicide rates among patients with genitourinary cancers and identify factors associated with suicide in this specific cohort. METHODS: Patients with prostate, bladder, kidney, testis, and penile cancer were identified in the Surveillance, Epidemiology, and End Results database . Standardized mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 27 publications
(45 reference statements)
12
86
0
Order By: Relevance
“…Earlier research showed that older people tend to commit complete suicide among general population 19, 20. Older patients with cancer are also high‐risk group, which is consistent with our research 21, 22, 23. Older patients usually encountered with greater disease burden, and social psychological pressure.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier research showed that older people tend to commit complete suicide among general population 19, 20. Older patients with cancer are also high‐risk group, which is consistent with our research 21, 22, 23. Older patients usually encountered with greater disease burden, and social psychological pressure.…”
Section: Discussionsupporting
confidence: 91%
“…Although the SEER dataset precludes information regarding adverse effects of definitive treatment (notably, ED and UI), the fact that RP or RT did not lend to a heightened risk for suicide is telling (given the significant impact of these adverse effects on health-related quality of life [10,11,23,25,27]) and corroborates previous findings [11,14]. The no-treatment cohort in our present study may have included men who were poor-risk candidates for definitive treatment secondary to pre-existing comorbidities; however an attempt was made to mitigate this selection bias by including only men were recommended treatment by their physician but either refused or otherwise did not receive it.…”
Section: Discussionsupporting
confidence: 80%
“…radiation or surgery. Besides, men with metastatic disease have consistently been shown to harbour higher risk of suicidal death [5,13,14,28,40], and their inclusion in the current analysis may have limited the internal validity of our present results.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations